A novel highly bio‐available itraconazole formulation (SUBA®‐Itraconazole) for anti‐fungal prophylaxis in lung transplant recipients. Issue 4 (1st March 2021) - Whitmore, Timothy James; Yaw, Meow; Lavender, Melanie; Musk, Michael; Boan, Peter; Wrobel, Jeremy
Abstract: Background: Antifungal prophylaxis remains a mainstay of lung transplantation, given invasive fungal infection is a common and serious complication after lung transplantation. Choice of systemic agent to prevent invasive fungal infection varies between centers and funding of agents remains challenging. Our center has recently changed from posaconazole to a highly bioavailable formulation of itraconazole (SUBA®‐itraconazole) at substantially reduced cost, but safety and toxicity require further assessment. A retrospective study of lung transplant patients receiving systemic antifungal prophylaxis from December 2016 through December 2019 following change from posaconazole to itraconazole as standard practice. 150 patients with lung transplants were managed in this time period, with 88 (59%) receiving at least 1 mold‐active triazole during the study period. 48 (58%) of these patients received SUBA®‐itraconazole; 68 (82%) received posaconazole and 10 (12%) received voriconazole. The average cost per patient during the study period was significantly lower on SUBA®‐itraconazole (mean 1548/patient/6 month course) than posaconazole (mean 16 921.35/patient/6 month course). Target trough concentrations for prophylaxis of itraconazole > 0.5 mg/L and posaconazole > 0.7 mg/L were achieved on empiric dosing in 49% and 68% respectively. Overall trough itraconazole (0.50 vs 1.12 mg/L, P < .001) and posaconazole (1.37 vs 2.10 mg/L P < .001) concentrations were significantly lower in patients with cystic fibrosis. Calcineurin inhibitor dose changes on introduction or cessation were similar for SUBA®‐itraconazole and posaconazole. Breakthrough invasive fungal infection and toxicity were rare. SUBA®‐itraconazole is well‐tolerated, associated with rare breakthrough invasive fungal infection, and lower cost. Prospective studies following general introduction are required to determine long‐term safety, tolerability, and efficacy.